OCEANIC PLATEAUS: PROBLEMATIC PLUMES, POTENTIAL PARADIGMS - Kerr A.C.; Mahoney J.J. (My University, 2007)
Oceanic plateaus are vast areas (> 2 × 105 km2) of thicker than average oceanic crust (up to 38 km) that typically are elevated 2-3 km above the surrounding seafloor. Because of their thick, relatively high-standing crust, portions of oceanic plateaus can accrete to convergent continental margins and thus have contributed to continental growth over time. Through studies of accreted oceanic plateau sections and from drilling of in-situ plateaus, knowledge of plateau structure, composition and age has increased considerably over the last 20 years. However, models for the origin of oceanic plateaus are still not without significant problems. Mantle plume models can explain many of the observed chemical and physical features, but other characteristics are not readily explicable by conventional thermal plume models. This is particularly true of the largest plateau, the Cretaceous Ontong Java Plateau in the western Pacific. If formed by a plume head, much of the surface of this plateau should have become subaerial, but instead largely appears to have erupted at water depths > 1000 m; furthermore, post-eruption subsidence was much less than predicted by thermal plume models. Other models, such as meteorite impact-induced melting and spreading-induced upwelling of eclogite, are also fraught with problems. A solution to the anomalous uplift and subsidence of the Ontong Java Plateau may lie in its derivation from a thermochemical mantle plume. Modelling suggests such plumes can consist of large amounts of compositionally dense material, thereby reducing net plume buoyancy. Future work should explore in detail the capabilities of thermochemical plumes, the role of oceanic plateaus in continental growth, and links between the formation of plateaus and major environmental crises such as oceanic anoxic events. © 2007 Elsevier B.V. All rights reserved.
Keywords: CARIBBEAN PLATEAU; KERGUELEN PLATEAU; OCEANIC PLATEAU; ONTONG JAVA PLATEAU; THERMOCHEMICAL PLUME; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая